Pengembangan Media Pembelajaran Geometri Berbantuan Software Autograph - Nasution, Mikasari; Hidayat, Hidayat (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted because there were students who had difficulty understandinggeometry material in optimally learning the coordinate system in addition, the lack of development of learning media with a touch of creative and innovative technology. This study aims to develop Geometry learning media in the form of learning videos assisted by Autograph Software. This study uses the ADDIE Model which consists of three stages, namely Analysis, Design (design), Development (development). The test subjects in this study were experts, one media expert, one material expert and one teacher. Data collection techniques used in this development in the form of interviews and questionnaires. Data analysis techniques used are qualitative and quantitative. Based on the validation, according to media experts, they got a score of 4.2 in the